Determination of the microplastic particle release by tea bags during brewing - Kirill Nikolaevich, Kornilov; Nataliya Nickolaevna, Roeva (Journal of Engineering & Processing Management, 2021)
The presence of microscopic particles of plastic (MP) in food is currently an urgent problem in the modern food industry and one of the main issues of food safety. However, there are no clear methods for the determination of such particles, nor methods for cleaning food products from them. In the present work, for the first time, the method of Dynamic Laser Light Scattering (DLS) was used to determine the plastic nanoparticles from tea bags when they were boiled in boiling water. It has been established that some of the studied samples of sachets release a huge amount of such nanoparticles into water. Moreover, hundreds of millions of nanoparticles are released per one microscopic particle.